2018
DOI: 10.1038/s41401-018-0061-3
|View full text |Cite
|
Sign up to set email alerts
|

Isoalantolactone suppresses LPS-induced inflammation by inhibiting TRAF6 ubiquitination and alleviates acute lung injury

Abstract: Isoalantolactone (IAL) is a sesquiterpene lactone extracted from roots of Inula helenium L and has shown anti-inflammatory effects. In this study we investigated the therapeutic effects of IAL on acute lung injury (ALI) and elucidated the mechanisms underlying its anti-inflammation potential in vitro and in vivo. Treatment with lipopolysaccharide (LPS, 100 ng/mL) drastically stimulated production of inflammatory mediators such as NO, TNF-α, IL-1β, and IL-6 in mouse bone marrow-derived macrophages (BMDMs), whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 60 publications
3
29
0
Order By: Relevance
“…walls, is generally recognized as the key factor to induce ALI. Challenge with LPS can result in inflammatory cell infiltration, generate a large number of pro-inflammatory cytokines, and then cause the lung tissues damage (Huang et al, 2018;Ding et al, 2019). In the present study, we found that treatment of PIC significantly reversed the increases of cell infiltration and the levels of pro-inflammatory cytokines including TNF-a and IL-1b both in lung and BALF induced by LPS.…”
Section: Discussionsupporting
confidence: 61%
“…walls, is generally recognized as the key factor to induce ALI. Challenge with LPS can result in inflammatory cell infiltration, generate a large number of pro-inflammatory cytokines, and then cause the lung tissues damage (Huang et al, 2018;Ding et al, 2019). In the present study, we found that treatment of PIC significantly reversed the increases of cell infiltration and the levels of pro-inflammatory cytokines including TNF-a and IL-1b both in lung and BALF induced by LPS.…”
Section: Discussionsupporting
confidence: 61%
“…Through the years, many of SLs have been reported to be effective on treatment of inflammation. For example, isoalantolactone, a sesquiterpene lactone extracted from roots of Inula helenium L, was identified to suppress LPS-induced lung injury and proinflammatory cytokine expression [10]; budlein A can reduce the proinflammatory cytokines and neutrophil recruitment in a model of acute gout arthritis [34]. DHL is a sesquiterpene lactone which has been extensively reported to exhibit anti-tumor and hepatoprotective activities [20,21,35], while the effect of DHL on ALI is rarely examined.…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS), a main component of bacterial cell walls, has been identified as a key factor in ALI/ ARDS development. Exposure to LPS causes inflammatory cell infiltration, leading to generation of cytokines and chemokines that subsequently lead to initiation and propagation of the inflammation response seen in ALI/ARDS [10]. LPS binds Toll-like receptor 4 (TLR4) on the cell surface which then stimulates the recruitment and activation of the adaptor protein myeloid differentiation primary response gene 88 (MYD88) to the receptor complex, in turn leading to the activation of intracellular pathways [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, the data from our research showed that IAL is potentially useful for the treatment of S. aureus pneumonia when used in combination with β-lactam antibiotics. In addition, IAL was administered by subcutaneous administration at a dose of 30 mg/kg, which had no macroscopic toxic effects, and no obvious adverse reactions were observed in C57/BL6 mice after intraperitoneal injection with IAL (20 mg/kg) [19,21].…”
Section: Discussionmentioning
confidence: 99%
“…Isoalantolactone (IAL), a eudesmanolide-type sesquiterpene flavonoid compound, has been isolated from Atalantia buxifolia, Artemisia, Carpesium cernuum and Inula helenium, and has been shown to have anti-inflammatory, anticancer, antiparasitic and antivirulence activities [17][18][19][20]. In addition, pharmacological research found that this natural compound is a promising candidate for the treatment of carcinoma in humans [21]. However, the effect of IAL on resistance-related enzymes has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%